IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR - Rahman Wahid, - (2020)
This study examines the implementation of multicultural education in elementary schools. The purpose of this study was to determine the implementation, obstacles and solutions, as well as the impact of multicultural education in the Islamic elementary school Al-Amanah Kecamatan Cileunyi Bandung Regency. The approach used in this research is a qualitative approach using the case study method. Participants in this study were schools that included teachers, principals, vice-principals in the curriculum, and students. The instruments used in this study were interviews and document analysis. Data analysis techniques used are Miles and Huberman which include data reduction, data display, and data verification. The results showed that Al-Amanah Islamic Elementary School had implemented multicultural education quite well, including through a policy of mutual respect and tolerance in the rules and customs of school culture. In addition, the school program also supports the implementation of multicultural education such as the large number of extracurricular activities and annual programs such as performing arts, cultural studies, and degrees of creativity. Meanwhile, in the process of learning the integration of multicultural content, especially in Civics subjects, this is done in a way that uses demonstration learning methods and role playing. Barriers experienced by schools in the implementation of multicultural education include the lack of multicultural poster media and students' sense of social concern that still needs to be improved. While the impact felt by schools on the implementation of multicultural education is the creation of a family climate and a sense of mutual tolerance among school residents.